2019
DOI: 10.3389/fmicb.2019.00005
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Comparisons Among the Genus Shewanella Reveal the Enrichment of Genes Encoding Ankyrin-Repeats Containing Proteins in Sponge-Associated Bacteria

Abstract: The bacterial members of the genus Shewanella are widely distributed and inhabit both freshwater and marine environments. Some members of Shewanella have gained considerable attention due to its ability to survive in redox-stratified environments. However, a gap of knowledge exists on the key genomic features of the sponge-associated Shewanella sp. involving the successful host-bacteria interaction, as sponge-symbiotic Shewanella are largely underrepresented in the public repositories. With the aim of identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 90 publications
0
13
0
Order By: Relevance
“…Two new sponge-associated cyanobacterial draft genomes belonging to the newly described Leptothoe genus were recovered from the isolates TAU-MAC 1615 and 1115 ( Figure S1 , Table 1 ). To date, most microbial isolates derived from sponges have been mainly affiliated with Proteobacteria [ 7 , 25 , 26 ]. A limited number of cyanobacterial strains have been isolated from sponges [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two new sponge-associated cyanobacterial draft genomes belonging to the newly described Leptothoe genus were recovered from the isolates TAU-MAC 1615 and 1115 ( Figure S1 , Table 1 ). To date, most microbial isolates derived from sponges have been mainly affiliated with Proteobacteria [ 7 , 25 , 26 ]. A limited number of cyanobacterial strains have been isolated from sponges [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Genes encoding eukaryotic-like proteins (ELPs) such as ankyrin-like domains (ANKs), tetratricopeptide repeats (TPRs), Leucine-rich repeat (LRR) protein, and pyrroloquinoline quinone (PQQ) were detected in the two sponge-associated Leptothoe strains (Table 2); ELPs are often detected in facultative or obligate symbionts and play a key role in the modulation of cellular protein-protein interactions [37,38]. In particular, abundance of ANKs seems to be a major genomic feature of sponge symbionts [6,26] as they have The sponge-associated strains possess biosynthetic gene clusters (BGCs) encoding for natural products despite undergoing genome reduction (Figure 4a,b). It has been proposed that maintenance of such clusters sustains the symbiotic interaction [35].…”
Section: Eukaryotic-like Protein (Elp)-encoding Genesmentioning
confidence: 99%
“…Furthermore, the protein sequences of the Endozoicomonas genomes were scanned against local InterPro's proteins signature database using InterProScan v5.32-71.0 [42]. The output files were screened for the protein domains using InterPro entries-ANKs (IPR020683 and IPR002110), TPRs (IPR011990, IPR019734, IPR013105, IPR001440, and IPR011717), and Sel1 (IPR006597) as previously reported [7,43]. In order to avoid false prediction due to high similarity of proteins containing TPRs and Sel1 repeat, TPRpred v10.3-a profile-based tool was used to classify TPRs and Sel1 repeats within a protein using E-value cutoffs of 10 −3 and 10 −2 [44].…”
Section: Prediction Of Symbioses Factors and Secretion Systemsmentioning
confidence: 99%
“…Our recent study reported that the genome of Shewanella sp. OPT22 and S. spongiae KCTC 22492 isolated from sponges are enriched with genes coding for ANKs when compared to other Shewanella strains inhabiting other niches [7]. The role of ANKs from sponge symbionts in modulating the amoebal phagocytosis was experimentally validated [81].…”
Section: Symbioses-related Genes In Endozoicomonas Sp Opt23mentioning
confidence: 99%
See 1 more Smart Citation